Precipitation behaviour and mechanical properties during short‑term heat treatment for tailor heat treated profiles (THTP) of aluminium alloy 6060 T4 - Fröck, Hannes; Graser, Matthias; Milkereit, Benjamin; Reich, Michael; Lechner, Michael; Merklein, Marion; Kessler, Olaf (Materials Science Forum, 2017)
Precipitation hardening aluminium alloys are widely used for automotive applications. To enhance the application of aluminium profiles, improved formability is needed. Tailor Heat Treated Profiles (THTP) with locally different material properties attempt to increase formability e.g. in bending processes. Tailoring of local properties is obtained by a local short-term heat treatment, dissolving the initial precipitate state (retrogression) and still allowing subsequent ageing. In the present study, the dissolution and precipitation behaviour of the aluminium alloy EN AW-6060 T4 was investigated during heating with differential scanning calorimetry (DSC). Heating curves from 20 to 600 °C with heating rates of 0.01 up to 5 K/s were recorded. Interrupted heat treatments with different maximum temperatures were performed in a deformation dilatometer. Immediately afterwards, tensile tests were carried out at room temperature. The course of the recorded mechanical properties as a function of the maximum temperature is discussed with regard to the dissolution and precipitation behaviour during heating. Finally, the aging behaviour of the investigated alloy was recorded after different typical short-term heat treatments and is discussed with reference to the DSC‑curves. The correlation of the microstructure and the mechanical properties enables the derivation of optimal parameters for the development of THTP through a local softening.
CRIS-Team Scopus Importer:2023-03-29
Keywords: Differential scanning calorimetry; Dissolution; EN AW-6060; Precipitation; Re-aging; Tailor heat treated profiles (THTP)